Effect of plastic waste shredding and its mixture formula on increasing the compressive strength of earth bricks - Bebhe, Kristiana; Purwanto, LMF; Hermawan, Hermawan (Edelweiss Applied Science and Technology, 2025)
Plastic waste is a global problem that threatens the environment because it is difficult to decompose and can damage ecosystems. The large amount of plastic waste that has not been processed poses environmental risks as well as depletes local white soil resources, which are valuable for building materials. These factors strongly motivate the recycling of plastic waste and white soil into quality building products. This study aims to recycle and examine the effects of shredding four types of plastic waste and variations in mixture formulas with white soil and cement to improve the compressive strength of white soil brick building materials in Kupang, East Nusa Tenggara, Indonesia. White soil is a calcareous soil with different characteristics from the clay commonly used as a basic material for brick making. Ordinary soil materials are less capable of integrating with plastic waste without melting it first. In contrast, white soil is limestone-based, containing calcite, which can function as an adhesive. White soil makes up coral islands and limestone hills. In this study, four types of plastic waste were used: PET (Polyethylene Terephthalate), LDPE (Low-Density Polyethylene), PP (Polypropylene), and PS (Polystyrene), as part of the mixture for making white soil bricks. The method employed was an experimental approach involving the production of plastic waste-white soil bricks with three variations of mixture formulas combining plastic waste, white soil, and cement as an adhesive. The compressive strength test was conducted to observe the effects of the four types of plastic waste and the different formulas on the weight and compressive strength of the white soil bricks. Results showed that the use of plastic waste in manufacturing white soil bricks significantly affected compressive strength and reduced weight. All waste types contributed to increased compressive strength, especially LDPE waste, which reached a maximum of 100.3 kg/cm². The most effective formula was a mixture of 1 part cement, 1 part plastic waste, and 7 parts white soil. The compressive strength of these plastic waste-white soil bricks meets the requirements for concrete bricks according to Indonesian National Standard-03-0349-1989 and can be used as wall materials per Indonesian National Standard 03-6881.1-2000. The novelty of this research lies in demonstrating the ability of four types of plastic shreds without melting and identifying the most effective formula for producing lightweight, high-quality composite bricks from local white soil and plastic waste materials.